2022
DOI: 10.3390/polym14050884
|View full text |Cite
|
Sign up to set email alerts
|

Leachability and Anti-Mold Efficiency of Nanosilver on Poplar Wood Surface

Abstract: Water-based antimicrobial agents, used in environmentally friendly applications, are widely used in wood protection industries. Furthermore, nanomaterials as antimicrobial agents, because of their biocidal component, huge specific surface area, and unique nanoscale effect, have attracted attention in the field of biodurability. We employed aqueous dispersed nano-silver with a diameter of 10 nm~20 nm to treat poplar wood and evaluated its leaching resistance and anti-mold effect on the wood surface. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Correspondingly, the SEM morphologies showed that compared with the control group, where abundant spores and hyphae of both the fungi appeared on the cell walls (Fig. 2), there were no hyphae present on the cell walls of SIM impregnated wood, suggesting that SIM effectively inhibited the reproduction of fungi (Dai et al 2022).…”
Section: Anti-mould Agent Loading and Anti-mildew Evaluationmentioning
confidence: 85%
See 2 more Smart Citations
“…Correspondingly, the SEM morphologies showed that compared with the control group, where abundant spores and hyphae of both the fungi appeared on the cell walls (Fig. 2), there were no hyphae present on the cell walls of SIM impregnated wood, suggesting that SIM effectively inhibited the reproduction of fungi (Dai et al 2022).…”
Section: Anti-mould Agent Loading and Anti-mildew Evaluationmentioning
confidence: 85%
“…1.25wt% SIM impregnated wood samples showed that the wood vessels were covered by microcapsules, some gathered around and inside the grain holes of wood. It would be bene cial to the nanoscale effect (Dai et al 2022), and in return positively contribute to the inhibition e cacy of SIM against the mold fungi. 0.5wt% SIM impregnated wood samples showed relatively few microcapsules, but the microcapsules still attached to wood grain holes.…”
Section: Morphology and Size Distribution Of Simmentioning
confidence: 99%
See 1 more Smart Citation
“…Dai et al [ 101 ] applied water-based nano silver to carry out antibacterial modification treatment on the surface of the wood and characterized its antibacterial properties. The experimental findings demonstrated that when the retention rate of silver reached 0.324 g·m −2 , the antibacterial rates of the wood surface for three kinds of molds, namely Aspergillus niger V. Tiegh, Penicillium citrinum Thom, and Trichoderma viride Pers.…”
Section: Improvement Of Antibacterial Properties Of the Wood Surfacementioning
confidence: 99%
“…Pine wood impregnated with silver nanoparticles showed lower values of weight loss caused by T. versicolor than the control wood [ 96 ]. Silver nanoparticles dispersed in water exhibited a strong protection efficiency of the poplar wood surface against the molds A. niger , P. citrinum , and T. viride [ 188 ]. Impregnation with titanium dioxide nanoparticles of eight wood species ( Pinus sylvestris L., Abies alba M., Juglans regia L., Castanea sativa M., Prunus avium L., Quercus petraea L., Fagus sylvatica L., and Fraxinus excelsior L.) prevented the growth of the rot fungi H. lixii (white rot) and M. circinelloides (brown rot), irrespective of the wood species [ 189 ].…”
Section: Synthetic Antifungal Agentsmentioning
confidence: 99%